1-(6,8-Dibromo-2-methylquinolin-3-yl)ethanone - Prasath, R. (International Union of Crystallography, 2011)
Two independent molecules,1 and 2, with similar conformations comprise the asymmetric unit in the title compound, C(12)H(9)Br(2)NO. The major difference between the molecules relates to the relative orientation of the ketone–methyl groups [the C—C—C—C torsion angles are −1.7 (6) and −16.8 (6)° for molecules 1 and 2, respectively]; in each case, the ketone O atom is directed towards the ring-bound methyl group. The crystal packing comprises layers of molecules, sustained by C—H⋯O and π–π {ring centroid(C(6)) of molecule 2 with NC(5) of molecule 1 [3.584 (3) Å] and NC(5) of molecule 2 [3.615 (3) Å]} interactions. C—H⋯Br contacts also occur.